In vitro study on bacterial leakage up to half of the canal length in different post-space preparation methods after root canal obturation - Phan, Anh Chi; Le, Thi Thu Nga; Nguyen, Thi Ngoc Lan; Le, Thi Bao Chi (Tạp chí Y Dược Huế, 2025)
Introduction: A common cause of failure in endodontic treatment is bacterial penetration into the root canal system through microleakage after obturation, particularly when post-space preparation is required. Objective: To evaluate bacterial leakage in post-space prepared to half the root canal length using different methods following root canal obturation. Subjects and Methods: An in vitro study, without a control group, was conducted on 40 mandibular premolars, which were divided into 4 groups according to the obturation method and the timing of post-space preparation. Bacterial leakage was assessed by the turbidity of the BHI solution in each group, and Gram staining was performed if turbidity appeared. Results: Group 1 exhibited a delayed bacterial leakage time compared to Group 2. Additionally, Group 3 showed a later leakage time than Group 4. However, Group 1 had an earlier bacterial leakage time compared to Group 3, and Group 2 had an earlier leakage time than Group 4. The differences were statistically significant (p < 0.05). Gram-positive bacteria (90%) and Gram-negative bacteria (10%) were identified in the group with lateral compaction obturation. In the group with thermoplasticized Gutta Percha obturation, only Gram-positive bacteria (100%) were found. Conclusion: Immediate post-space preparation resulted in a significantly delayed bacterial leakage compared to delayed post-space preparation. Post-space preparation in teeth obturated with thermoplasticized Gutta Percha resulted in a significantly delayed bacterial leakage compared to those obturated using the lateral compaction technique.